Use of Integrative Medicine in the United States Military Health System - Madsen, Cathaleen (Evid Based Complement Alternat Med, 2017)
Integrative medicine (IM) is a model of care which uses both conventional and nonconventional therapies in a “whole person” approach to achieve optimum mental, physical, emotional, spiritual, and environmental health, and is increasingly popular among patients and providers seeking to relieve chronic or multifactorial conditions. The US Department of Defense (DoD) shows particular interest in and usage of IM for managing chronic conditions including the signature “polytrauma triad” of chronic pain, traumatic brain injury (TBI), and posttraumatic stress disorder (PTSD) among its beneficiaries in the Military Health System (MHS). These modalities range from conventional nondrug, nonsurgical options such as cognitive-behavioral therapy to nonconventional options such as acupuncture, chiropractic, and mind-body techniques. These are of particular interest for their potential to relieve symptoms without relying on opiates, which impair performance and show high potential for abuse while often failing to provide full relief. This review describes the use of IM in the MHS, including definitions of the model, common therapies and potential for use, and controversy surrounding the practice. More research is needed to build a comprehensive usage analysis, which in turn will inform sound clinical and financial practice for the MHS and its beneficiaries.